Wave runup parameterization for sandy, gravel and platform beaches in a fetch-limited, large estuarine system. (1st January 2020) - Didier, D.; Caulet, C.; Bandet, M.; Bernatchez, P.; Dumont, D.; Augereau, E.; Floc'h, F.; Delacourt, C.
Abstract: Empirical models of wave runup are commonly derived from open beaches, but their applicability in fetch-limited, sheltered environments are yet to be properly assessed. Based on original video-derived runup observations on 5 beaches with distinct morphodynamic states in the Estuary and Gulf of St. Lawrence (EGSL), this paper presents a runup analysis at the regional scale. A wide range of environmental parameters (varying wave climate, beach slopes, tidal range) and beach types (platform-beach, with and without nearshore bars, sandy/gravel) are considered. A total of 430 15 min timestacks have been analyzed over 35 different days across a 3-year survey. Runup, setup, incident ( f > 0.05 Hz) and infragravity ( f < 0.05 Hz) swash are regressed against offshore wave characteristics and beach slope. Results indicate that the influence of the hydrodynamic parameters on wave runup, setup and swash is a function of offshore wave height and wavelength. While hydrodynamic forcing explain most of the coastal water level components variability, setup and swash are affected differently by the beach slope. The role of the beach morphology on wave setup can be parameterized through the inverse function of the beach slope, while swash height is written as the square root of the beach slope. The parameterizations of R 2 % for the EGSL beaches have been validated against a new set of observations. Overall, the hydrodynamic forcing is the dominant driver of wave runup, but including the beach slope improves the understanding of the runup components. The original formulations offer a strong potential for runup assessment on various morphological fetch-limited coastal environments. Highlights: Video observations of runup on 5 beaches in the Estuary and Gulf of St. Lawrence. Original parameterizations of wave runup on mixed sand/gravel sheltered beaches. The offshore wave forcing influence on runup is parameterized under a constant form. The influence of beach morphology on runup is a function of the beach slope. For steep (mild) slope, the swash (setup) dominates the wave runup dynamic.